2018
DOI: 10.3329/jujbs.v7i2.40742
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irrigation salinity on the growth and yield of two Aus rice cultivars of Bangladesh

Abstract: The experiment was conducted to clarify the growth and yield response of two rice cultivars, BR55 and BR43 under salt stress. Six different concentrations of NaCl viz 50, 100, 150, 200, 250 and 300 mM and distilled water (control) were applied on the rice cultivars which were grown under pot culture condition. Growth parameters like plant height, tiller number, leaf number and leaf area were negatively affected by salinity in both cultivars. Salt stress caused a significant reduction in yield in both cultivars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…In our study, all markers generated polymorphic banding patterns where a total of 53 alleles were detected across the genotypes with an average of 4 alleles per locus which was compatible with the previous work of Ali et al, (2004). The number of alleles detected is one of the selection categories in assessing a marker's usefulness in diversity analyses since a higher allele count per locus means that the marker is able to discriminate genotypes that might be indistinguishable to other markers (Khanam et al, 2018). In our study gene diversity at each SSR locus was significantly correlated with the number of alleles detected, number of repeat motif and with the allele size range.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, all markers generated polymorphic banding patterns where a total of 53 alleles were detected across the genotypes with an average of 4 alleles per locus which was compatible with the previous work of Ali et al, (2004). The number of alleles detected is one of the selection categories in assessing a marker's usefulness in diversity analyses since a higher allele count per locus means that the marker is able to discriminate genotypes that might be indistinguishable to other markers (Khanam et al, 2018). In our study gene diversity at each SSR locus was significantly correlated with the number of alleles detected, number of repeat motif and with the allele size range.…”
Section: Discussionsupporting
confidence: 86%
“…However, when the plants were 8 weeks after planting, the plant height of three rice tested was higher when planted in non-saline compared grown in 8 dS m -1 . The decrease of plant height under 8 dS m -1 due to negative impact of salinity by inhibiting the photosynthesis rate, changes of enzyme activity, and decreasing of carbohydrate production [14]. According to the research of Alam et al salt concentration above 8.5 up to 12.5 dS m -1 caused a decrease of plant height in BR5828-11-1-4 rice cultivar up to 45% compared to the control [15].…”
Section: Resultsmentioning
confidence: 96%
“…It has been proven that 50 mM NaCl stress reduces plant height, tillering, leaf relative RWC, chlorophyll and yield ( Naim, 2014 ). Khanam et al (2018) and others also proved that 50 mM salt stress in pot experiments will have negative effects on the plant height, tiller number, leaf number and leaf area of rice. However, in the experiment of Hariadi et al (2015) , we found that 50 mM salt stress could not significantly inhibit the growth of some salt-tolerant varieties.…”
Section: Discussionmentioning
confidence: 94%